THE EFFECT OF SCIENTIFIC LITERACY INTEGRATION WITH CASE-BASED LEARNING MODEL ON STUDENTS’ CRITICAL-THINKING SKILLS - NUR ROHMAH, SITI; NISWATI RODLIYATUL JAUHARIYAH, MUKHAYYAROTIN (Inovasi Pendidikan Fisika, 2020)
This study aims to describe the effect of the integration of scientific literacy in the Case-Based Learning (CBL) model of students critical thinking skills. This type of research is a quasi-experimental design with quantitative descriptive analysis techniques, and the research design used is non-equivalent control group design. The subjects of this study were students of class XI Even Semester Academic Year 2019/2020 at SMAN 1 Gondang Nganjuk. The data used is a written test obtained from the results of pre-test and post-test, then analyzed using inferential statistics One-way ANOVA. The analysis shows that learning with the integration of scientific literacy in the CBL model influences students critical thinking skills. Learning with the integration of scientific literacy in the CBL model increases the critical-thinking skills of students with high categories, wherein the ?experimental class 1?, ?experimental class 2?, and the ?control class? get an N-gain score of 0.73, 0.72, and 0.35 respectively. Based on the N-gain score shows that the increase in critical thinking skills in the experimental class is higher than the control class. It can conclude that the integration of scientific literacy in the CBL model influences students critical thinking skills. Therefore, the integration of science literacy in the CBL model can further applied to other physics materials to improve critical-thinking skills. Keywords: Case-Based Learning (CBL), scientific literacy, critical-thinking skills